STRATEGI AUSTRALIA MEMASUKKAN INDONESIA KE DALAM BUKU PUTIH PERTAHANAN (DEFENCE WHITE PAPER) 2013 - Imam, Muhammad; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the strategy of Australia insert Indonesia into Australia Defence White Paper 2013. Defence White Paper is one of strategic products in the field of defence, which is an outline of the statement and the defence policy as a guidelines for organizing the defence of state functions. Different to the previous White Paper, Defence White Paper 2013 discussed Indonesia more specific with emphasis on sub-chapter in this Paper. One of priority of Australia defence interest is to maintain the good relations with Indonesia.The theory that applied in this research is realisms paradigm with the level analysis is Nation-State Analysis. The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles, internet and other media. This research focused on why Australia insert Indonesia into Australia Defence White Paper 2013. Using strategic theory from John P. Lovell about Accommodation Strategy and the cooperative security concept by J.E. Nolan.The research found that Indonesia has more powerful military force in the aggregate compared than Australia, among others are manpower, naval power, land system, air power, and resources. Australia looked to Indonesia as a country that has successfully rebuilding the democracy, economy, and military and that is the interest of Australia to continue a good relations with Indonesia. Australia build the security cooperation that provide benefits to prevent various threats that threatening it’s national security. The aim of this strategy is to deterrence the treats that come to Australia and maintain the stability of national security by building a strategic relation with Indonesia.Keywords: strategy, australia, defence white paper, indonesia